The Effect of Removable Dentures on The Oral Mucosa of The Prosthetic Area (Open Herald: Periodical of Methodical Research, 2023)
Removable prostheses have a combined mechanical, chemotoxic, sensitizing and thermally insulating irritating effect on the mucous membrane of the prosthesis base and its neuroreceptive organs, the intensity and nature of which depend on the physico-chemical properties of the prosthesis base, design features, manufacturing quality and duration of use of the prosthesis